Predictors of Infections and Mortality in Adult Patients Undergoing Extracorporeal Membrane Oxygenation. (4th October 2017) - Viotti, Julia Bini; Cloke, Christina; Shaikhomer, Mohammed; Grant, April; Ghodsizad, Ali; Brozzi, Nicolas; Loebe, Mathias; Abbo, Lilian M
Abstract: Background: Extracorporeal membrane oxygenation (ECMO) has been used in various clinical settings, such as acute respiratory distress syndrome, cardiogenic shock and refractory septic shock. One of the associated risks is acquisition of infections during bypass because of the multiple cannulation sites. The purpose of this study was to evaluate the predictors of healthcare associated infections (HAI) and mortality in adult patients on ECMO. Methods: This was a retrospective descriptive study at a 1550 bed University- affiliated tertiary medical center in Miami, Florida. We looked at patients over 18 years old on ECMO for > 48 hours between January 1–August 31, 2016. The presence of an infection before ECMO placement or acquired during ECMO support were noted. Only culture- proven infections were included. The primary outcome was to identify risk factors associated with HAI or mortality. Results: 40 patients undergoing ECMO during the study period were identified. 25 patients met the inclusion criteria and were included in the analysis. During a total of 364 ECMO days, 12 patients out of 25 had microbiologically proven infection (48 %). There were 7 ventilator associated pneumonias (41%), 5 bacteremias (29%), 2 pleural empyemas (12%), 2 Clostridium difficile colitis (12%) and 1 mediastinitis (6%). Candida species were the predominant blood isolates (60%). The rate of infection per 1, 000 ECMO days was 46.7. The overall in-hospital mortality was 64%. There was no impact of infection on mortality, length of ICU, or hospital stay. ECMO use for < 7 days was associated with overall less episodes of infection vs ECMO use for > 7 days. (P-value 0.0136, OR 0.089, CI: 0.01–0.6). Charlson-comorbidity score of 5 or more was associated with higher episodes of bacteremia ( P  = 0.0023, OR = 16, CI = 1.38–185.41). Conclusion: Infections did not have an impact on mortality. Patients on ECMO for less than 8 days had less episodes of infections. Patients with Charlson-comorbidity index of 5 or more were associated with higher episodes of bacteremia. Further prospective cohort studies are necessary to address causality and to determine infection and mortality predictors that can be modified for patients undergoing ECMO. Disclosures: All authors: No reported disclosures.